Comparative case studies in integrated care implementation from across the globe: a quest for action (2019)
Background: Integrated care is the coordination of general and behavioral health and is a highly promising and practical approach to improving healthcare delivery and patient outcomes. While there is growing interest and investment in integrated care implementation internationally, there are no formal guidelines for integrated care implementation applicable to diverse healthcare systems. Furthermore, there is a complex interplay of factors at multiple levels of influence that are necessary for successful implementation of integrated care in health systems. methods: Guided by the Exploration, Preparation, Implementation, Sustainment (EPIS) framework (Aarons et al., 2011), a multiple case study design was used to address two research objectives: 1) To highlight current integrated care implementation efforts through seven international case studies that target a range of healthcare systems, patient populations and implementation strategies and outcomes, and 2) To synthesize the shared and unique challenges and successes across studies using the EPIS framework. Results: The seven reported case studies represent integrated care implementation efforts from five countries and continents (United States, United Kingdom, Vietnam, Israel, and Nigeria), target a range of clinical populations and care settings, and span all phases of the EPIS framework. Qualitative synthesis of these case studies illuminated common outer context, inner context, bridging and innovation factors that were key drivers of implementation. Conclusions: We propose an agenda that outlines priority goals and related strategies to advance integrated care implementation research. These goals relate to: 1) the role of funding at multiple levels of implementation, 2) meaningful collaboration with stakeholders across phases of implementation and 3) clear communication to stakeholders about integrated care implementation.